Homer and the Bible in the eyes of ancient interpreters - Niehoff, Maren (Jerusalem studies in religion and culture., 2012)
The present collection of articles brings together scholars from different fields and offers prioneering essays on the Alexandrian scholia, Philo, Platonic thinkers and the rabbis, which cross traditional boundaries and interpret Biblical and Homeric readers in light of each other.